Positive Reaction Toward Trade and Economic Partnership Between Indonesia and Australia Governments in The Jakarta Post - Rosaria Mita Amalia; Taufik Ampera; Yuyu Yohana Risagarniwa (Intermestic: Journal of International Studies, 2019)
This study explores the representation of social actors, both in the Indonesian and Australian governments on the Trade and Economic Partnership through Critical Discourse Analysis approach. The issue focuses on both governments partnership published in the Jakarta Post during 2014-2018. Using Critical Discourse Analysis as an approach, this article analyses the media exclusion and inclusion strategies of social actors. By applying descriptive qualitative methods, result shows that the dominant strategy is the inclusion strategy. The use of inclusion strategy indicates specifications, individualization and categorization of positive reaction and support of The Jakarta Post towards the Indonesian government on trade and economic partnership between Indonesia and Australia. However, the use of exclusion strategy is aim to hide the social actors in the discourse and to divert reader's attention to the object rather than the subject discourse.